If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(w + 7) = -9w + -27 Reorder the terms: -3(7 + w) = -9w + -27 (7 * -3 + w * -3) = -9w + -27 (-21 + -3w) = -9w + -27 Reorder the terms: -21 + -3w = -27 + -9w Solving -21 + -3w = -27 + -9w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '9w' to each side of the equation. -21 + -3w + 9w = -27 + -9w + 9w Combine like terms: -3w + 9w = 6w -21 + 6w = -27 + -9w + 9w Combine like terms: -9w + 9w = 0 -21 + 6w = -27 + 0 -21 + 6w = -27 Add '21' to each side of the equation. -21 + 21 + 6w = -27 + 21 Combine like terms: -21 + 21 = 0 0 + 6w = -27 + 21 6w = -27 + 21 Combine like terms: -27 + 21 = -6 6w = -6 Divide each side by '6'. w = -1 Simplifying w = -1
| 3r-2=-10+7r-3r | | 14b=-224 | | -4p-3(3-4p)=3(p-5)-34 | | 5(5x+1)-5=25x+0 | | m+4=n+10 | | -2d-9d-(-15d)=-20 | | -2(c-8)=-2c-8 | | (3+3j)(9-2j)= | | -9y=10-8y | | 5+7x-28=2-8x+64 | | 10x=5+15 | | -[2z-(11z+3)]=3+(8z+2) | | 9s-9s+5s=15 | | k-(-1)=-5 | | -9=-10-8 | | (-8x+2)+(10x-7)= | | 5n+10=4n | | 331=6x+7x | | (-5m^2+6n^2-7n)-[(6m^2-7m+5n)+(-6m^2)+4n^2]= | | 3x^2+8x-10=x^2+7x+5 | | bx+by=18 | | -16v+18v-(-11)=-13 | | 6(x+1)+4=-6(x-7)-9 | | 9j-9+4j=-9-2j | | 195=70+(10+8)w | | =11a^2b-12ab^2 | | x+(-4)=-2 | | 20n-4=15n+15 | | 3n+2n-7=8 | | 2x-10+65-1x=85 | | m+12=-18 | | -1.5t^2+36t+6=0 |